The Nature of Evolution: A Study on the Philosophy of A.M. Iqbal - Imam Bahroni (At-Ta'dib, 2012)
The nature of human being evolution in the philosophy of AllamaMuhammad Iqbal is different from the conception of other modernphilosophers. This natural evolution basically springs from the real Love whichflourishes in the inner being of an individual.Love as described by Iqbal is not physical, sexual or biological principle.It is the inward drive of all life to attain to its full maturity and development. Itis a primal urge to live, to progress and bring out all the inner wealth andresources of being. Every phenomenon and activity that is not related to thisprimal urge and does not subserve its purposes, leads to stagnation and decay.He voices strong condemnation of scientific reason, arts and religion whenthey carve out for themselves autonomous fields of action or set themselvesup as independent forces. According to Iqbal, all specialized activity, whether itis intellectual, artistic or religious, is a differentiation of the primal urge whichhe calls Love and apart from it has no title to independent, autonomous existence.Iqbal further explains that a philosophy which does not spring from thedepth of life is so much empty trash; and thought which is not inspired by loveor the will to progress, construct, create and beautify the world is dreadening.Similarly a religion without the flame of love of the urge to advance, improveand enrich life is only lifeless ritualism. Disbelief and atheism are as good asIslam, if inflamed by love, while Islam is no better than paganism if it is devoid of Love.